A comparative study on slim 3-D receiver coil structures for omnidirectional wireless power transfer applications. Issue 2 (6th September 2019) - Wu, Minxin; Zhong, Wenxing; Tan, Siew Chong; Hui, S. Y. R.
Abstract: This paper presents a comparative study on three types of slim coil structures used as a three-dimensional (3-D) receiver in a wireless power transfer system with a planar transmitter coil. The mutual coupling values and their variations between the receiver structures and the transmitter coil are compared under different distances and angular orientations with respect to the transmitter coil. The merits of performance are related to the consistency of the mutual coupling values under different orientations in a range of distances from the transmitter coil. The practical results show that slim 3-D receiver coil structures can be compatible with a planar transmitter coil with reasonably high-mutual coupling.